Developing a motorized seatbelt positioning mechanism Designing to accommodate all passenger sizes through concept development for shoulder interaction in rear seats of cars - Smedberg, Love; Ström, Gustaf (My University, 2026)
Seatbelt positioning is critical for occupant safety. However, a fixed position is not optimal for all occupants and is instead a compromise. When a seatbelt is positioned too close to the neck, it causes discomfort, which frequently leads to dangerous misuse, such as placing the seatbelt under the arm. While front seats are typically equipped with manual adjustment mechanisms, these are unsuitable for the rear seats, especially for children, as manual functions are often ignored or improperly used in these positions. The project was conducted at Volvo Cars and followed a structured product development process aimed at continuously increasing knowledge and concept maturity while strategically narrowing the design space to maintain design freedom in early stages. To define the problem space, a stakeholder analysis was conducted to map stakeholder needs for the mechanism. The system’s functions were analyzed to generate possible sub-solutions to be synthesized into concepts using a morphological matrix. These concepts were subsequently systematically screened based on critical requirements utilizing an elimination matrix. Furthermore, the concepts were comparatively evaluated based on a set of criteria using the Pugh matrix. The Kesselring matrix further complemented the evaluation process with weighted criteria and more defined scoring to identify the most suitable solution for the application. Throughout the development process, several activities were utilized, including brainstorming sessions, modeling in CAD, rapid prototyping, and physical testing. While the final concept, "Rack and Roll", featuring a rack and pinion mechanism driven by a stepper motor, is proven to be functionally capable, it remains a proof-of-concept rather than an optimized production unit. The results indicate that an automated seatbelt positioning system is highly feasible and scalable for high-volume production. However, further development, design modifications, and rigorous testing are required before final integration into passenger vehicles.
Keywords: webbing; seatbelt; mechanism; mechatronic; adaptive; lateral; ositioning; rapid prototyping; deflect; motor; back row; C-pillar